Emerging Adults' Exposure to and Postings About Substance Use on Social Media: An Observational Study. Issue 6 (December 2022) - Burnell, Kaitlyn; Andrade, Fernanda C.; Hoyle, Rick H.
In a community sample of emerging adults ( N = 232), this study (a) assessed participants' exposure to and postings about alcohol, cigarettes, e-cigarettes, and marijuana across social media platforms, (b) investigated how exposure to and posting about text versus visual substance-related content differentially relate to one's own use, and (c) tested if exposure to versus posting about substances differentially relate to use. Data were collected via cross-sectional, daily, and observational methods. Participants were frequently exposed to substances on social media. Postings were less common, with Snapchat a notable outlet. Visual posts were somewhat more prominently linked to one's own use than text posts. Posting about substances tended to be more strongly associated with own use than exposure, but this did not necessarily replicate with observed assessments. Social media platforms are key for emerging adults to encounter and post about substance use content, with implications for emerging adults' own substance use.